Chronic iron overload causing haemochromatosis and hepatopathy in 21 horses and one donkey - Theelen, M.J.P.; Beukers, M.; Grinwis, G.C.M.; Oosterbaan, M.M. (British Equine Veterinary Association, 2019)
Background: Iron toxicosis is rarely reported in horses and chronic excessive oral iron intake has not been reported to cause clinical symptoms in equids. Objectives: This case series describes 21 genetically unrelated horses and one donkey with chronic iron overload causing haemochromatosis and hepatopathy. Study design: Case series. Methods: All equids showing clinical signs compatible with chronic liver disease presented to Utrecht University and diagnosed with iron overload and haemochromatosis based on histopathological evaluation of liver tissue and/or blood transferrin saturation levels of >80% and proof of excess dietary iron intake due to excess iron content in drinking water were included. Results: This study included 22 equids. All tested animals (n = 19) had transferrin saturation >80% and 21 of 22 had increased gammaglutamyltransferase (cGT). Ultrasonography revealed rounded liver margins in five out of six horses and increased echogenicity in 4/6. Histological examination of liver tissue of 12 animals showed hepatitis, fibrosis and haemosiderin accumulation in macrophages and hepatocytes. Post-mortem examination also revealed haemosiderin accumulation in other organs in all seven examined animals. High iron content in drinking water was identified as the source of iron overload in all cases. All animals were housed under the same conditions for a minimum of 9 years prior to diagnosis of haemochromatosis. Of 22 animals, 13 survived until 1 January 2018, ranging from 17 to 79 months post diagnosis. Main limitations: Histology of liver tissue was not available for 10 of 22 cases. Conclusions: Chronic iron overload can lead to haemochromatosis and hepatopathy in equids. Development of disease is slow and clinical signs are nonspecific. Long-term excessive iron intake in equids should be avoided. If animals drink from natural water sources, it is important to test the water for iron content.
Keywords: horse; iron toxicosis; liver failure; iron toxicity; liver disease; iron saturation; haemosiderin; Taverne; SDG 3 - Good Health and Well-being